Investigation of the efficacy of synbiotics in the treatment of functional constipation in children: a randomized double-blind placebo-controlled study - Baştürk, Ahmet; Artan, Reha; Atalay, Atike; Yılmaz, Aygen (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: The aim of this study was to demonstrate the efficacy of synbiotic (Lactobacillus casei, L. rhamnosus, L. plantarum, and Bifidobacterium lactis and prebiotics [fiber, polydextrose, fructo-oligosaccharides, and galacto-oligosaccharides]) treatment in children with functional constipation. Materials and Methods: This study was performed in patients aged 4-18 years, and the patients were diagnosed to have functional constipation according to the Roma III diagnostic criteria. In this prospective study, the first group received synbiotic and the second group received a placebo. At the end of 4 weeks, patients were questioned about the initial symptoms. Patients who showed improvement in the initial symptoms at the end of the 4-week treatment period were considered to completely benefit from the treatment and those with some improvement in initial symptom were considered to partially benefit from the treatment. Results: The synbiotic and placebo groups comprised 72 and 74 patients, respectively. The mean age in the whole study group was 9.18±3.48 years with a male:female ratio of 1:21. After 4 weeks of treatment, significant improvement was not observed in any of the findings in the placebo group. Conversely, a significant improvement was observed in the weekly number of defecations, abdominal pain, painful defecation, and pediatric Bristol scale (p≤0.001) in the synbiotic group. Complete benefit from the treatment was achieved in 48 (66.7%) and 21 (28.3%) patients in the synbiotic and placebo groups, respectively, and a significant difference was observed between the groups (p≤0.001). Conclusion: Our studies have shown that the use of synbiotics in the treatment of functional constipation in children is beneficial. Cite this article as: Baştürk A, Artan R, Atalay A, Yılmaz A. Investigation of the efficacy of synbiotics in the treatment of functional constipation in children: a randomized double-blind placebo-controlled study. Turk J Gastroenterol 2017; 28: 388-93.